2021
DOI: 10.1088/1361-6463/ac3c77
|View full text |Cite
|
Sign up to set email alerts
|

Highly responsive multi-flow pattern generation by multi-electrode plasma actuator using a single power supply

Abstract: A dielectric-barrier-discharge plasma actuator (DBD-PA) is an active flow-control device that uses ionic wind generated by electrohydrodynamic forces. A DBD-PA controls fluid motion and offers quick response without the need for moving parts. Previous studies have proposed methods for generating various flow patterns with a DBD-PA for fluid control. This paper presents a method for generating multiple flow patterns using a multi-electrode DBD-PA that is driven by a single-channel high-voltage power supply with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This phenomenon is referred to as 'electric wind' or 'ionic wind' [5,21,22]. It leads to the formation and development of a starting vortex [23][24][25][26] or a directionally controllable wall jet [27,28]. Experimental data indicated that the time-averaged velocity induced by plasma can reach a few m•s −1 [5,6,11,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is referred to as 'electric wind' or 'ionic wind' [5,21,22]. It leads to the formation and development of a starting vortex [23][24][25][26] or a directionally controllable wall jet [27,28]. Experimental data indicated that the time-averaged velocity induced by plasma can reach a few m•s −1 [5,6,11,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that a negative pulse is more efficient and produces a stronger pressure wave than a positive one under low dissipated power [15,32], and the deposition energy shows a strong dependency on the thickness of the dielectric [29]. Furthermore, given the propagation length of the discharge along the dielectric surface is generally less than 20 mm [38], three-electrode [26,28,34,40] and multi-SDBD actuators [27,37] are used to enlarge the surface discharge area, and simultaneously increasing the range of plasma-based flow control. When arranging several single SDBD units in series, the interaction between adjacent single SDBDs should be taken into consideration [41].…”
Section: Introductionmentioning
confidence: 99%